Effects of Suspension Training on Core Stability and Functional Movement Screen Scores in Healthy Adult Men - Young Jun Kim; Moon Young Choi; Gi Chul Ha (Asian Society of Kinesiology, 2023)
OBJECTIVES The purpose of this study is to determine whether suspension training can be an effective intervention in improving functional movement in healthy adult men. METHODS The recruited subjects of Twenty healthy adult men without musculoskeletal diseases were divided into group that performed TRX exercise (n=10) and a group that performed traditional OKC exercise using a resistance machine (n=10). The variables were the deep squat, hurdle step, inline lunge, shoulder mobility, leg raise, push-up, and rotational stability after an 8-week exercise program. The total score of the 7 movements was calculated to compare and analyze the before-and-after changes in FMS score. All the data obtained in this study were analyzed with SPSS package (ver 21.0). To examine the effects of the suspension training program used in this study, Repeated measures ANOVA was conducted to compare the effects before and after the participation in the program. RESULTS The research results are as follows; The results of the FMS evaluation scores showed no significant differences between the TRX group and the OKC group in the deep squat, hurdle step, inline lunge, shoulder mobility, leg raise, and push-up evaluations, and no interaction effect was found. However, the rotational stability evaluation score showed higher scores in the TRX group after training, showing a significant interaction effect (p<.001). The change in total evaluation score also significantly increased in the TRX group (p<.05), but there was no significant difference in the OKC group. CONCLUSIONS In conclusion, rotational stability and total evaluation scores increased after training in the TRX group. In particular, TRX training using suspension may be more effective than traditional forms of training using resistance exercise equipment for people who have instability in the multi-plane stability of the pelvis, core, and shoulder girdle, which are involved in rotational stability.